O perfil epistemológico do conceito de espaço em alunos do curso de licenciatura em física - Buscatti Junior, Donizete Aparecido [UNESP] (2014)
One of concepts used in physics class is the concept of space. Although textbooks treat in this concept in a simple way, a more careful analysis shows that it has undergone various interpretations over the historical process. The notion of epistemological profile of Gaston Bachelard (1884-1962) divides this plurality in diferent areas of the profile: Naive Realism, Empiricism, Rationalism Simple and Complete. In this sense, the central concern of this research was to investigate how future teachers in Physics (students of Graduation) conceive the notion of space. Therefore, it was invsetigated in the first half of the year 2013, a sample of students who attended the course of Supervised Internship in Physics UNESP Presidente Prudente/SP. Inititally we applied a questionnaire with closed and open questions to raise initial conceptions. Then these students performed a chronicle of class (a simulation class) to the teacher and colleagues specifically addressing the concept of space. Finally the researcher conducted an interview with students. Data were transcribed and analyzed in light of the Bachelardean. The data showed that students had no notion of the plurality of the concept of space and the experience of the individual strongly influences your individual profile